An in-situ X-ray computed tomography imaging apparatus with stack pressures for rechargeable batteries. (May 2023) - Miao, Ning; Hai, Bo; Wang, Shanfeng; Ni, Jun; Li, Xiang; Wei, Hang; Zhang, Kai; Wang, Xiaolong; Huang, Weifeng
Abstract: Herein, a novel in-situ X-ray computed tomography (CT) imaging apparatus with stack pressures is proposed to detect the micro-structural evolution at the interface during the electrochemical process. And the relationship between the electrochemical performance and the interface morphology of lithium metal batteries has been effectively investigated through this in-situ technology. It can be observed that the growth of Li dendrites and their morphology evolution are directly dependent on the stack pressures. The Li dendrite grows from the needle-structure to the island-structure, accompanied by the tip-growth mode transferring to the base-growth mode in the range of the critical pressure. Moreover, the growth of Li dendrites can also be effectively inhibited when loading a suitable stack pressure. This novel in-situ CT imaging technology provides a feasible way to underlying the interface micro-structure evolution, electrochemical-pressure complexions, and safety of next-generation rechargeable batteries. Graphical abstract: Image, graphical abstract